Induction Apoptosis of Erinacine A in Human Colorectal Cancer Cells Involving the Expression of TNFR, Fas, and Fas Ligand via the JNK/p300/p50 Signaling Pathway With Histone Acetylation - Lee, Ko-Chao; Lee, Kam-Fai; Tung, Shui-Yi; Huang, Wen-Shih; Lee, Li-Ya; Chen, Wan-Ping; Chen, Chin-Chu; Teng, Chih-Chuan; Shen, Chien-Heng; Hsieh, Meng-Chiao; Kuo, Hsing-Chun (Frontiers in Pharmacology, 2019)
Erinacine A, which is one of the major bioactive diterpenoid compounds extracted from cultured mycelia of H. erinaceus, displays great antitumorigenic activity. However, the molecular mechanisms underlying erinacine A inducing cancer cell apoptosis in colorectal cancer (CRC) remain unclear. This study found that treatment with erinacine A not only triggers the activation of extrinsic apoptosis pathways (TNFR, Fas, FasL, and caspases) but also suppresses the expression of antiapoptotic molecules Bcl-2 and Bcl-XL via a time-dependent manner in DLD-1 cells. Furthermore, phosphorylation of Jun N-terminus kinase (JNK1/2), NFκB p50, and p300 is involved in erinacine A–induced cancer cell apoptosis. Inhibition of these signaling pathways by kinase inhibitors blocks erinacine A–induced transcriptional activation implicates histone H3K9K14ac (Acetyl Lys9/Lys14) of the TNFR, Fas, and FasL as promoters. Moreover, histochemical and immunohistochemical analyses revealed that erinacine A treatment significantly induced the TNFR, Fas, and FasL levels in the in vivo xenograft mouse model. Together, these results demonstrated an increase in the cellular transcriptional levels of TNFR, Fas, and FasL by erinacine A induction to cell apoptosis via the activation of the JNK, p300, and NFκB p50 signaling modules, thereby providing a new mechanism for erinacine A treatment in vitro and in vivo.